Inflammatory arthritis in systemic sclerosis is associated with elevated C-reactive protein and requires musculoskeletal ultrasound for reliable detection - Feldmann, Daria; Jandova, Ilona; Heilmeier, Ursula; Kollert, Florian; Voll, Reinhard E.; Finzel, Stephanie (Frontiers in Medicine, 2023)
Objectives. About 25% of patients with systemic sclerosis (SSc) have elevated C-reactive protein (CRP) levels. Specific causes of CRP elevation are unknown so far. We aimed to investigate whether inflammatory arthritis is associated with CRP elevation. Furthermore, we evaluated the sensitivity and specificity of clinical examination compared to musculoskeletal ultrasound (MSUS) for detection of arthritis. Methods. Sixty-five patients with SSc (51 females) were enrolled and allocated into a CRP-positive (CRP+, n=20; CRP elevated for at least two years prior to enrolment) and a CRP-negative (CRP-; n=45) cohort. All patients were examined clinically (modified Rodnan Skin Score, mRSS; swollen/tender joint count 66/68), received a comprehensive MSUS of their hands and feet, as well as laboratory testing (antibody status; CRP). Statistical analyses were performed using non-parametrical tests without adjustments. Results. Patient with a disease duration <3 years had higher CRP levels (p=0.042). Anti-centromere antibodies dominated in CRP- patients (p=0.013), and anti-Scl70 antibodies in CRP+ patients (p=0.041). Joint effusion and B-mode synovitis prevailed in male (p<0.00001; p<0.0001) and CRP+ (p=0.001; p<0.00001) patients. Power Doppler (PD)-synovitis predominated in patients with diffuse SSc (p=0.0052). Joint effusion and B-/PD-synovitis were mostly confined to wrists, MTPs and talo-navicular joints. Compared to MSUS, sensitivity of clinical examination was as low as 14.6%; specificity was 87.7%. Sensitivity was reduced by the presence of soft tissue edema or a mRSS >10. Conclusions. Arthritis is more frequent in CRP+ compared to CRP- SSc patients. Compared to MSUS sensitivity of clinical examination is low for the detection of arthritis; this is likely due to skin fibrosis and soft tissue edema. Therefore, regular monitoring via MSUS should be considered as routine assessment in SSc patients.